The Application of BIM-Enabled Facility Management System in Complex Building - Wang, Jun; Li, S; Wang, Xiangyu; Mao, C; Guo, J (IGI Global, 2013)
Facility Management (FM) is well known for its interdisciplinary knowledge and along with the growingnumber of green buildings and low-carbon buildings, the FM system become increasingly complex. Many practitioners consider Building Information Modeling (BIM) as the most important technology to bring about improvements. The purpose of this paper is to develop a BIM-enabled FM system which integrates FM, BIM and building management system to improve information sharing and monitoring, FM system control, and equipment management. A case study is implemented to validate the feasibility of the BIM-enabled FM system. Four functionalities are demonstrated in detail: Equipment Information Monitoring (EIM), Dynamic Data Display and Warning (D3W), Energy-Saving Analysis (ESA), and Intelligent Fire Escape Route (IFER). The results show that BIM-enabled FM system facilitates the FM more accurate, timely, safe and efficient.